Future Fiscal and Budgetary Shocks - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2008)
We study the effects of future tax and budgetary shocks in a non-monetary and possibly non-Ricardian economy. An (unanticipated) temporary labor tax cut to be effective on a given future date—a delayed “debt bomb”—causes at once a drop in the (unit) value placed on the firms' business asset, the customer, with the result that share prices, the hourly wage, and employment drop in tandem. This paradox of reduced activity through announcement of future “stimulus” does not hinge on an upward jump of long interest rates. A future tax-rate cut lacking a “sunset” provision has the same negative effects.